ANALISIS FAKTOR PENENTU KINERJA KARYAWAN PATRA HOTEL DAN CONVENTION SEMARANG - Arif Sulistiyono; Jefri Heridiansyah; Theresia Susetyarsi (JURNAL STIE SEMARANG, 2020)
This research aims to find out: 1) The influence of work motivation on the performance performance of Patra Hotel and Convention Semarang employees. 3) Effect of work environment on the performance of Patra Hotel and Convention Semarang employees. 4) The effect of work discipline on the performance of Patra Hotel and Convention Semarang employees. The population in this study were 150 employees of Patra Hotel and Semarang Convention. The sample of Patra Hotel and Convention Semarang employees 2) The influence of leadership on the of this study were 60 employees of Patra Hotel and Convention Semarang. The results found that: 1) Work motivation has a significant effect on employee performance (β) 0.388 with a sig value of 0,000 <0.05. 2) Leadership has a significant effect on employee performance (β) 0,277 with sig value 0,001 <0,05 3.) Work environment has a significant effect on employee performance of (β) 0,256 with sig value 0,000> 0,05. 4) Work Discipline has a significant effect on employee performance of (β) 0.382 with sig 0.002 <0.05.